Culture Degeneration Reduces Sex-Related Gene Expression, Alters Metabolite Production and Reduces Insect Pathogenic Response in Cordyceps militaris - Peter A. D. Wellham; Abdul Hafeez; Andrej Gregori; Matthias Brock; Dong-Hyun Kim; David Chandler; Cornelia H. de Moor (Microorganisms, 2021)
Cordyceps militaris is an entomopathogenic ascomycete, known primarily for infecting lepidopteran larval (caterpillars) and pupal hosts. Cordycepin, a secondary metabolite produced by this fungus has anti-inflammatory properties and other pharmacological activities. However, little is known about the biological role of this adenosine derivate and its stabilising compound pentostatin in the context of insect infection the life cycle of C. militaris. During repeated subcultivation under laboratory conditions a degeneration of C. militaris marked by decreasing levels of cordycepin production can occur. Here, using degenerated and parental control strains of an isolate of C. militaris, we found that lower cordycepin production coincides with the decline in the production of various other metabolites as well as the reduced expression of genes related to sexual development. Additionally, infection of Galleria mellonella (greater wax moth) caterpillars indicated that cordycepin inhibits the immune response in host haemocytes. Accordingly, the pathogenic response to the degenerated strain was reduced. These data indicate that there are simultaneous changes in sexual reproduction, secondary metabolite production, insect immunity and infection by C. militaris. This study may have implications for biological control of insect crop pests by fungi.